THE EFFECT OF LEADERSHIP, ORGANIZATIONAL CULTURE AND COMPETENCY ON EMPLOYEE PERFORMANCE WITH WORKING DISCIPLINES AS INTERVENING VARIABLES IN THE KSOP OFFICE FOR SPECIAL BATAM - Rohmat, Abdurr; Satriawan, Bambang; Indrayani, Indrayani; Khaddafi, Muammar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study was to analyze the influence of leadership, organizational culture and competence on employee performance with work discipline as an intervening variable at the Batam Special KSOP Office. The study population consisted of 122 Civil Servants and 36 Honorary Batam Special KSOP Office. The sample selection method used was simple random sampling, which is a random sampling of the population based on the probability frequency of all members of the population. The spread of the questionnaire was carried out on 36honorary employees of the Batam Special KSOP Office. The data analysis technique used to solve the problem in this research is quantitative analysis technique, namely path analysis with the application of multiple linear regression models using the help of the SPSS 24.0 program. The results of this study indicate that Leadership and Competence have a significant positive effect on Work Discipline. Organizational Culture has a positive but not significant effect on Work Discipline. Furthermore, leadership has a positive and significant effect on employee performance. Organizational Culture has a positive and insignificant effect on Employee Performance. Competence has a negative and insignificant effect on employee performance. As for the work discipline variable, it has a positive but insignificant effect on employee performance.